PERAN PT. KAWANUA KAHURIPAN PANTERA (KKP) TERHADAP KONDISI SOSIAL EKONOMI MASYARAKAT DI KECAMATAN PINOLOSIAN, KABUPATEN BOLAANG MONGONDOW SELATAN - Angelina ., Tumandung; Theodora M. Katiandagho; Eyverson ., Ruauw (Sam Ratulangi University, 2018)
This study aims to see how big the role of PT. Kawanua Kahuripan Pantera (KKP) Against the economic social conditions of Pinolosian District of South Bolaang Mongondow District.The study was conducted from November 2016 to July 2017 (from preparation to report generation). The data used is primary data. This research is done by direct interview technique with company leader, employees as much (30 people), and Village Head (Sangadi) Pinolosian Subdistrict. The data obtained will be analyzed using descriptive analysis and will be presented in tabular form.The results of this study indicate the role of PT. KKP to socio-economic of Pinolosian Sub-district is public facility (Help for mosque and church worship place such as material fund for development and renovation), mangrove planting as many as 935 trees, clovepod assistance 26,510 pieces, job opportunity (Job Opening). In addition the company also provides health benefits for workers and affects the economy (Income) of the workers.